The Effect Of Secang Wood Detection Water In Treating Prickly Heat In Infants 0-12 Months - Marliah; Misrawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Secang wood decoction can be used to treat prickly heat of the infants Aged 0-12 months because secang wood contains gallic acid, flavonoids, tannins, resins, resorcin, d-alpha-phellandrene, oscimene, essential oils and brazilin which function as anti-bacterial, anti-inflammatory, anti-biotic and anti-oxidant. This study aimed to determine the effect of giving water Decoction of Secang Wood in Healing Prickly Heat in Babies Aged 0-12 Month in the working area of the Kassi-Kassi Makassar public Health Center in makassar in 2021. The type of research conducted is quantitative research Quasi-Experimental approach. sampling technique ussing Purposive Sampling with Posttest-only Control Group Design.The respondents of this study were 30 babies, 15 babies in the treatment group and 15 control group babies. Secang wood boiled water is used for bathing baby 2 times a day for 7 days. After being given sappan wood boiled water monitoring the healing of prickly heat with statistical tests using the Chi-Square test. The results showed that 15 babies were given boiled water seccang wood has the result of healing prickly heat (100%), meanwhile Of the 15 babies who were not given sappan wood boiled water, there were 2 babies who were experienced recovery (13.3%) and 13 infants who did not recover (86.7%). The results after statistical tests were carried out using the Chi-Square test the value of ρ = 0.000 < α = 0.05 is obtained, then H0 is rejected and Ha is accepted. So it can be concluded that in this study there is influence Giving Water Boiled Secang Wood in Healing Prickly Heat Infants Aged 0-12 Months in the Kassi-Kassi Makassar Health Center Working Area 2020. As advice for mothers whose babies experience prickly heat, you can applying the use of boiled water of secang wood to cure the prickly heat sweat in babies, so they can avoid prickly heat.